2021
DOI: 10.13057/ijap.v11i1.46525
|View full text |Cite
|
Sign up to set email alerts
|

Interpretasi Tingkat Kekerasan Batuan Bawah Permukaan di Daerah Rawan Gempa Bumi Kota Bengkulu

Abstract: <p class="AbstractText">Bengkulu City is located in the subduction zone of the Indo-Australian and Eurasian plates, so it is prone to earthquake. To anticipate the impact of earthquake, disaster mitigation can be carried out, one of which is a study of the level of rock hardness in the area. This study aims to determine the level of rock hardness based on seismic wave velocity in several rock formations and to determine which rock formations have the potential to cause vulnerability to earthquakes. Field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Previous research on subsurface rock structures in the Bengkulu city has been researched by Lestari (2018), (Hadi et al, 2021), and (Simbolon et al, 2020). Lestari (2018) conducted research using Multichannel Analysis of Surface Wave (MASW) and USGS data on f0 from microtremor measurements in Bengkulu City.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on subsurface rock structures in the Bengkulu city has been researched by Lestari (2018), (Hadi et al, 2021), and (Simbolon et al, 2020). Lestari (2018) conducted research using Multichannel Analysis of Surface Wave (MASW) and USGS data on f0 from microtremor measurements in Bengkulu City.…”
Section: Introductionmentioning
confidence: 99%
“…However, the method using the Vs30 value can only identify a soil depth of 30 meters. (Hadi et al, 2021) carried out research in Bengkulu City using the MASW method with a time-term inversion technique to obtain bedrock that varies from the surface to a depth of 17.71 m. While, (Simbolon et al, 2020) showed that they used the geomagnetic method to identify rock structures to a depth of 1 km. Based on previous study, it is vital to analyze the subsurface structure deeper than the methods that have been used.…”
Section: Introductionmentioning
confidence: 99%
“…Sebagai daerah yang dilewati jalur gempa, Provinsi Bengkulu berada didaerah rawan gempa dimana gempa bumi ringan dan sedang seringkali terjadi dalam frekuensi yang cukup tinggi. Berdasarkan peta pembagian wilayah gempa yang ada (SNI 03-1726(SNI 03- -2002 dan Pedoman Perencanaan Ketahanan Gempa untuk Rumah dan Gedung tahun 1987, Bengkulu berada pada wilayah zona 5 dan sebagian masuk ke dalam zona 6 yang memiliki koefisien gempa 0,25 dan 0,30, yaitu wilayah yang memiliki potensi gempa yang tinggi (Hadi et al, 2021).…”
unclassified